Evolution of dirofilariasis diagnostic techniques from traditional morphological analysis to molecular-based techniques: a comprehensive review - Aththanayaka, A.M.M.T.B.; Dayananda, B.S.W.M.T.B.; Ranasinghe, H.A.K.; Amarasinghe, L.D. (Frontiers in Parasitology, 2024)
Dirofilariasis, caused by the nematode Dirofilaria spp., poses significant challenges in diagnosis due to its diverse clinical manifestations and complex life cycle. This comprehensive literature review focuses on the evolution of diagnostic methodologies, spanning from traditional morphological analyses to modern emerging techniques in the context of dirofilariasis diagnosis. The review traces the historical progression of diagnostic modalities, encompassing traditional approaches such as microscopic examination, serological tests (including ELISA and IFA), Radiographic imaging, Ultrasonography, Necropsy, which laid the foundation for subsequent advancements. The integration of molecular diagnostics marks a significant turning point in dirofilariasis diagnosis with the adoption of polymerase chain reaction (PCR) assays and real-time PCR (qPCR) facilitating enhanced sensitivity and specificity. Furthermore, recent strides in next-generation sequencing (NGS) technologies, including Whole Genome Sequencing (WGS), Targeted Sequencing (TS), Metagenomic Sequencing (MS), and RNA sequencing (Transcriptome Sequencing), have revolutionized the landscape of dirofilariasis diagnostics. Emerging techniques such as Loop-Mediated Isothermal Amplification (LAMP), Digital PCR (dPCR), and Digital microfluidics are also explored for their potential to augment diagnostic accuracy. The review addresses challenges associated with standardizing molecular protocols, tackling false positives/negatives, and discusses the advantages and limitations of each technique. By providing a comprehensive overview of dirofilariasis diagnostic strategies, from traditional to cutting-edge methods, this review aims to enhance understanding of the disease's diagnostic landscape. The insights gained have implications for improved disease management and guide future research endeavors toward refining diagnostic protocols and advancing therapeutic interventions.